Strategi Penerimaan Mahasiswa Baru Di Masa Pandemi - Ayu Veronika Somawati; Ida Bagus Putu Eka Suadnyana; I Made Hartaka (Jayapangus Press, 2021)
The current pandemic condition has a significant impact on all aspects of human life, including the education sector. Especially for universities, in the midst of situations where it is not possible to have face-to-face meetings with many people, a strategy is needed to increase the interest of prospective students who entrust their education to these universities. This is also a challenge for the Hindu Philosophy Study Program, STAH Negeri Mpu Kuturan Singaraja. As new study programs and universities, of course, a mature strategy is needed so that whatever is the strength of the Hindu Philosophy Study Program can be well socialized to the community. In addition, of course, the existing opportunities must also be maximized to overcome all existing threats. By using qualitative research methods, the data obtained were analyzed qualitatively to gain an in-depth understanding of the new student admissions strategy in the Hindu Philosophy Study Program at STAH Negeri Mpu Kuturan Singaraja during the pandemic.